2022
DOI: 10.1039/d2tc01889f
|View full text |Cite
|
Sign up to set email alerts
|

Twist-stacked 2D bilayer Fe3GeTe2 with tunable magnetism

Abstract: Controlling magnetism in two-dimensional (2D) magnetic compounds is of great significance for potential applications in novel spintronic devices. Based on the van der Waals monolayer, twist-stacking of bilayers can lead...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…From the DOS results, we found that the significant enhancement of the Fe-3d and S-3p hybridizations, as well as the reduced Fe–Fe distance, Li–Fe, Li–S, and Li–P bond lengths induced by the location of intercalated Li ions (in the interlayer vdW region), may the reason for the increase in MAE. 2…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the DOS results, we found that the significant enhancement of the Fe-3d and S-3p hybridizations, as well as the reduced Fe–Fe distance, Li–Fe, Li–S, and Li–P bond lengths induced by the location of intercalated Li ions (in the interlayer vdW region), may the reason for the increase in MAE. 2…”
Section: Resultsmentioning
confidence: 99%
“…48 Consequently, the spin-orbit coupling (SOC) effect, as well as its related exchange interaction, cannot be ignored and has been considered in our calculations. 2,3 The MAE of the three FPS bilayers is defined below as MAE = E 001 À E 100 or E 001 À E 010 , where E 100 , E 010 , and E 001 represent the total energies with an easy axis along the x-, y-and z-axes, respectively. We take the higher value of E 001 À E 100 and E 001 À E 010 as the value of MAE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…157 Afterwards, a similar situation was also observed in the twisted bilayer InSe, 158 in which the bandwidth can be suppressed to be less than 10 meV at θ = 9.43°. Recently, Chen et al proved that the two Fe 3 GeTe 2 layers can implement an antiferromagnetic–ferromagnetic phase transition by constructing an interlayer rotation, 159 providing a feasible method to tune the interlayer magnetic ordering of 2D compounds. These theoretical research studies adequately demonstrate that twist angle has a strong correlation with the magnetic, electrical and even optical properties of the materials.…”
Section: Controllable Fabricationmentioning
confidence: 99%